2003
DOI: 10.1080/0967026031000096227
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of the toxigenic dinoflagellatesAlexandrium tamarenseandA. ostenfeldiiin co-occurring natural populations from Scottish coastal waters

Abstract: Blooms of the toxic dinoflagellate Alexandrium tamarense (Lebour) Balech, a known producer of potent neurotoxins associated with paralytic shellfish poisoning (PSP), are common annual events along the Scottish east coast. The cooccurrence of a second Alexandrium species, A. ostenfeldii (Paulsen) Balech & Tangen is reported in this study from waters of the Scottish east coast. The latter species has been suspected to be an alternative source of PSP toxins in northern Europe. Recent identification of toxic macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 38 publications
2
96
0
Order By: Relevance
“…John et al (2003) also reported a substantial cell loss after hybridization of field samples. The major reasons for the low detection efficiency are most likely the screening and concentration processes for FISH involving several sieving and washing steps, resulting in considerable cell loss compared to the processing of samples for the Utermöhl method.…”
Section: Underestimation Of Cell Densities With Fishmentioning
confidence: 99%
See 2 more Smart Citations
“…John et al (2003) also reported a substantial cell loss after hybridization of field samples. The major reasons for the low detection efficiency are most likely the screening and concentration processes for FISH involving several sieving and washing steps, resulting in considerable cell loss compared to the processing of samples for the Utermöhl method.…”
Section: Underestimation Of Cell Densities With Fishmentioning
confidence: 99%
“…humic substances, might also have influenced the outcome by inhibiting the molecular procedure. In addition to this, cells in natural samples may sometimes be clumped or obscured by detrital particles, making the detection of target cells difficult (Scholin et al 1999, John et al 2003.…”
Section: Underestimation Of Cell Densities With Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…A. ostenfeldii is historically seen as background bloomer (Cembella et al, 2000;John et al, 2003), however, dense A. ostenfeldii blooms have been reported recently in the Narragansett Bay and the New River Estuary in the U.S. east coast (Borkman et al, 2012;Tomas et al, 2012), the Baltic Sea coast of Finland (Hakanen et al, 2012), along the Adriatic coast of Italy (Ciminiello et al, 2006), and recently in a creek of the Oosterschelde estuary in the Southwest of The Netherlands (Burson et al, 2014). This Oosterschelde estuary is a shallow, macrotidal and mesotrophic estuary with large stocks of mussels, oysters, and cockles ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…there is evidence that CIP toxins and their producers also are found in europe, the USA, and North Africa (Aasen et al, 2005a;Bire et al, 2002;Cembella and Krock, 2008;Ciminiello et al, 2006;John et al, 2003;MacKinnon et al, 2006;Marrouchi et al, 2010;Rundberget et al, 2011;touzet et al, 2008;Villar Gonzalez et al, 2006), and their presence, along with PSP to CTX also primarily in predatory fish consumed by humans (snapper, barracuda, amber jack and moray eel), and more investigations should be conducted on the role on Mtx in human intoxication.…”
Section: Ciguatera Fish Poisoning (Cfp) Toxinsmentioning
confidence: 99%